Conditional cash transfer and informality in Brazil - Ana Barbosa; Carlos Corseuil (IZA Journal of Labor & Development, 2014)
This study analyses the impact of Bolsa Família (a Brazilian conditional cash transfer programme) in the allocation of labour inputs regarding formal and informal activities. The methodology relies on a discontinuity in the programme eligibility rule regarding children's age to attain the identification of a LATE parameter. Our results suggest that the cash transfer does not affect the occupational choice of Brazilian adults neither among formal and informal jobs nor the allocation of hours across sectors.
Keywords: I38; O17; 330; Income transfer; Informal labour; Regression discontinuity design